Subcellular localization of Hairless protein shows a major focus of activity within the nucleus. - Maier, D.; Nagel, A.C.; Johannes, B.; Preiss, A. (Mechanisms of Development, 1999)
Hairless, a major antagonist of the Notch signaling-pathway in Drosophila (Bang and Posakony, 1992; Maier et al., 1992), associates with Suppressor of Hairless [Su(H)], thereby inhibiting trans-activation of Notch target genes (Brou et al., 1994). These molecular interactions could occur either at the step of signal transduction in the cytoplasm or during implementation of the signal within the nucleus. We examined the subcellular distribution of Hairless, showing that it is a low abundant, ubiquitous protein that is cytosolic as well as nuclear. High levels of Hairless cause nuclear retention of Su(H), loss of Hairless reduces the amount of Su(H) in the nucleus.